Modification of the terms of authorisation regarding the maximum inclusion level of Maxiban® G160 (narasin and nicarbazin) for chickens for fattening. (8th August 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; Pechová, Alena; et al.
Abstract: Following the request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the proposed modification of the terms of the authorisation regarding the maximum inclusion level of Maxiban ® G160. The FEEDAP Panel cannot conclude on the safety of Maxiban ® G160 at a dose level of 70 + 70 mg/kg feed for the target species. The use of Maxiban ® G160 in diets for chickens for fattening at the maximum proposed dose complies with the maximum residue levels (MRLs) in force of narasin and 4, 4'‐dinitrocarbanilide (DNC) at 0‐day withdrawal except for DNC in kidney which was slightly above the MRL. Compliance with DNC MRLs was seen in all tissues at 1‐day withdrawal. Based on the available data, the FEEDAP Panel cannot conclude on the safety of Maxiban ® G160 for the environment due to the risk identified for the terrestrial organisms due to DNC. Moreover, the high persistence and hydrophobicity of DNC indicate that there might be a risk for bioaccumulation but the risk for secondary poisoning was not identified. The potential of DNC to accumulate in soil over the years should be investigated by monitoring in a field study. The FEEDAP Panel would not be in the position to conclude on the efficacy of Maxiban ® G160 in chickens for fattening based on the data provided for the dose of 40 + 40 mg narasin + nicarbazin/kg feed.